Driving factors of formation, development, and change of spatial structure in metropolitan areas: A systematic review - Hashem Dadashpoor; Neda Malekzadeh (Journal of Urban Management, 2020)
In the last decades, there have been many articles on the spatial structure of metropolitan areas, but a study for explaining driving factors of changes in the spatial structure of metropolitan areas has remained unknown so far. To fill this gap, the article explains the driving factors of these changes using a systematic review method. To this end, 115 peer-reviewed scientific articles published from 1999 to 2019 were carefully analyzed. According to the results, 4 main dimensions including contextual and intrinsic, incentive and disincentive, developmental, and transformative were identified in this regard. This article argues that spatial structure subject to the driving factors have undergone vast changes over the past two decades, and the metropolitan areas have been shifting from concentrated and compact patterns toward decentralized and dispersed patterns.
Keywords: 710; Dispersion; Driving factor; Metropolitan areas; Monocentricity; Polycentricity; Spatial structure